Anti-SARS-CoV-2 IgG status among frontline health workers involved in COVID-19 survey at Jodhpur, Rajasthan, India - Vidhi Jain; Salman Khan; Neetha T Ramankutty; Kirti Vishwakarma; Akhil D Goel; Suman Saurabh; Pankaj Bhardwaj; Manoj K Gupta; Sanjeeta Dara; Ashok Kumar; Praveen Sharma; Vijaya Lakshmi Nag; et al. (Journal of Family Medicine and Primary Care, 2022)
Background: Asymptomatic carriers are responsible for the consistent spread of coronavirus disease 2019 (COVID-19) in the community. The Government of India has deputed house-to-house survey teams to aid in identifying asymptomatic individuals and their susceptible contacts. We selected door-to-door survey teams of a COVID-19 red zone in western India and determined their infectioncontrol practices and anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobin G (IgG) status. Materials and Methods: This single-day prospective cross-sectional study was conducted by the Department of Microbiology of a tertiary care hospital of Jodhpur, in collaboration with the Rajasthan State Health Services. Participants were asked to fill out a questionnaire regarding personal protective equipment (PPE) use after written informed consent. Venous blood samples were collected and Kavach enzyme-linked immunosorbent assay (ELISA) (J Mitra and Co.) was performed to determine anti-SARS-CoV-2 IgG status. Results: Out of the total 39 participants, IgG antibody was detected in four. Of them, three reported mild symptoms in the past. Out of two previously real-time polymerase chain reaction (RT-PCR) SARS-CoV-2-positive participants, only one had detectable IgG antibodies (Ab) in serum. Cloth mask was used by 24, N95 mask by 11, and surgical masks by four. Conclusion: Anti-SARS-CoV-2 IgG Abs were detected among four members of house-to-house COVID-19 survey teams in Jodhpur. Most of the team members used cloth masks, whereas the Government of India guidelines has recommended triple-layered surgical masks as minimum essential PPE for healthcare workers in India. More such studies should be conducted to ascertain infection prevention and control practices among such vulnerable frontline workers in our country.